Modified silver staining in 2DE improves protein detection even at extremely low sample concentration - Liew, Yun Khoon; Neela, Vasantha Kumari; Awang Hamat, Rukman; Amin Nordin, Syafinaz; Chong, Pei Pei (Wiley-VCH Verlag, 2013)
The typical concentration of protein loaded varies from 0.13 to 1.40 μg/μL for a classical silver staining method in 2DE gel. Here, we present a simple modified classical silver staining method by modifying the silver impregnation and development reaction steps. This modified method detects the protein spots at extremely low loaded concentrations, ranging from 0.0048 to 0.0480 μg/μL. We recommend this modified silver staining as an excellent method for the limited biological samples used for silver-stained 2DE analysis. Altogether, the protocol takes close to two days from first dimension separation to second dimension separation, followed by silver staining, scanning, and analysis.